Basics of Radiation Oncology - Miura, Masahiko (Shika Hoshasen, 2019)
Recently, advancement of the radiotherapeutic technologies for cancer treatment is striking and the clinical outcomes are greatly enhanced. More and more cancer patients are now receiving radiotherapy in Japan. In this situation, basic understanding of radiation oncology including radiobiology is essential especially for the JSOMFR-certified experts of dental radiology to realize recent radiotherapy for oral cancer. In this commentary, basics of radiobiology to understand the quantitative aspects of fractionated irradiation and characterization of some recent radiotherapeutic technologies will be described.